2020
DOI: 10.1063/5.0027995
|View full text |Cite
|
Sign up to set email alerts
|

Activation energies for two steps in the S2 → S3 transition of photosynthetic water oxidation from time-resolved single-frequency infrared spectroscopy

Abstract: Note: This paper is part of the JCP Special Topic on 65 Years of Electron Transfer.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 94 publications
1
26
1
Order By: Relevance
“…Early changes (50 µs after the 2nd flash) are observed around the water network at the PsbO-D2 interface (Fig. 5a ), which may indicate a fast, long-range electrostatically triggered proton release of surface carboxylates as found in PS II membrane particles from plants 14 , 62 . The short H-bonding interaction of E65 and R334 in the open state of the gate at 150 µs may indicate that a proton is already released from the gate in line with a suggested fast refilling of the earlier deprotonated site 62 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Early changes (50 µs after the 2nd flash) are observed around the water network at the PsbO-D2 interface (Fig. 5a ), which may indicate a fast, long-range electrostatically triggered proton release of surface carboxylates as found in PS II membrane particles from plants 14 , 62 . The short H-bonding interaction of E65 and R334 in the open state of the gate at 150 µs may indicate that a proton is already released from the gate in line with a suggested fast refilling of the earlier deprotonated site 62 .…”
Section: Discussionmentioning
confidence: 92%
“…5a ), which may indicate a fast, long-range electrostatically triggered proton release of surface carboxylates as found in PS II membrane particles from plants 14 , 62 . The short H-bonding interaction of E65 and R334 in the open state of the gate at 150 µs may indicate that a proton is already released from the gate in line with a suggested fast refilling of the earlier deprotonated site 62 . Alternatively, the gate may stay open until the proton is released in an apparent single proton hopping event occurring with Mn oxidation 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The S 2 → S 3 transition was studied in details [110,111], also by another research group [112]. In particular, results from the Noguchi group [107] suggested that during the S 2 → S 3 transition proton release is a rate-limiting step in the proton-coupled electron transfer.…”
Section: Photosystem II Reaction Centersmentioning
confidence: 99%
“…The faster phase with a t1/2 ≤ 25 µs is attributed to a proton transfer/release. This fast phase precedes the electron transfer from S2 to the TyrZ • that occurs with a t1/2 ≤ 300 µs [54][55][56][57][58]. It was discussed earlier that the fast phase could correspond to the release of a proton in an intermediate step S2 LS TyrZ  → S2 HS TyrZ  before the S2 HS TyrZ  → S3 S=3 transition occurs [35].…”
Section: Introductionmentioning
confidence: 87%